NUMERICAL METHODS AND IMPLEMENTATION IN GEOTECHNICAL ENGINEERING - PART 1 - Cheng, Y. M. (Frontiers in Civil Engineering Ser., 2020)
Numerical Methods and Implementation in Geotechnical Engineering explains several numerical methods that are used in geotechnical engineering. The first part of this reference set includes methods such as the finite element method, distinct element method, discontinuous deformation analysis, numerical manifold method, smoothed particle hydrodynamics method, material point method, plasticity method, limit equilibrium and limit analysis, plasticity, slope stability and foundation engineering, optimization analysis and reliability analysis. The authors have also presented different computer progr.